A Cross-Sectional Study of Psychological Status in Different Epidemic Areas in China After the COVID-19 Outbreak - Cao, Huan; Zuo, Chengchao; Li, Guo; Huang, Yaqi; Li, Ling; Huang, Shu; Zhao, Jianling; Liu, Jingjing; Jiang, Yongsheng; Wang, Furong (Frontiers in Psychiatry, 2020)
Background: The outbreak of coronavirus disease 2019 in Wuhan, Hubei Province, China has seriously affected people's mental health. We aimed to assess the psychological impact of the coronavirus disease 2019 on health care workers and non-health care workers in three different epidemic areas in China and to identify independent risk factors. Methods: We surveyed 1,020 non-health care workers and 480 health care workers in Wuhan, other cities in Hubei except Wuhan and other provinces in China except Hubei. Results: Health care workers in Hubei had higher levels of anxiety and depression than non-health care workers (p < 0.05), but there was no such difference in other provinces in China except Hubei (p > 0.05). Compared with other regions, health care workers in Wuhan was more anxious (p < 0.05), and this anxiety may be caused by concerns about occupational exposure and wearing protective clothing for a long time daily; health care workers in Hubei had more obvious depression (p < 0.05), which may be associated with long days participating in epidemic work and wearing protective clothing for a long time daily. Meanwhile, 62.5% of health care workers were proud of their work. The anxiety and depression of non-health care workers in Wuhan were also the most serious. Conclusions: In Wuhan, where the epidemic is most severe, levels of anxiety and depression seem to be higher, especially among health care workers. This information may help to better prepare for future events.